Guidance and Counseling Strategies for Addressing Online Game Addiction in Students - Desran Rivika; Rahma Wira Nita; Mori Dianto (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2021)
This study aims to describe the strategies employed by guidance and counseling teachers in addressing online game addiction among students, focusing on four service functions: prevention, understanding, alleviation, and advocacy. Using a qualitative descriptive approach, six informants were involved, including one counseling coordinator, two counseling teachers, one vice principal, and two students. Data were collected through interviews and analyzed using data reduction, presentation, and conclusion drawing. The findings reveal that preventive efforts were implemented through classical and group services with interactive methods and the use of a “Daily Pure Schedule” instrument to strengthen self-control. Understanding was fostered by providing digital literacy education and awareness of the risks of online game addiction through visual media such as educational videos and posters. Alleviation was conducted through individual counseling using Reality Therapy and home visits. Advocacy was carried out through smartphone restrictions, the formation of task forces, collaboration with parents via parenting groups, and coordination with internet café owners. Despite challenges such as student dishonesty and parental apathy, consistent advocacy fostered positive transitions, with parents becoming more cooperative. The study provides initial data for further research on online game addiction in broader educational contexts.